Molecularly imprinted fluorescence sensor chip for lactate measurement - Muersha Wusiman; Fariborz Taghipour (Microsystems & Nanoengineering)
Abstract Lactate measurements provide an opportunity to conveniently evaluate bodily functions and sports performance. A molecularly imprinted fluorescence biochip provides an innovative way to achieve lactate measurement and overcomes the limitations of enzyme-based sensors. To realize this goal, ZnO quantum dots (QDs), a biocompatible sensing material, were combined with selective receptors comprised of molecularly imprinted polymers (MIPs). The lactate-selective imprinted polymers were formed using 3-aminopropyltriethoxysilane (APTES) and 5-indolyl boronic acid monomers. Furthermore, a new solid-phase sensing platform that overcomes the limitations of liquid-based sensors was developed to detect lactate in real-time. The platform consists of the biosensor chip with a thin-film sensing layer, an ultraviolet (UV) excitation source, and a portable light detector. The final sensor has a sensitivity of 0.0217 mmol L-1 for 0–30 mmol L-1 of lactate in phosphate-buffered saline (PBS) with a correlation coefficient of 0.97. The high sensor sensitivity and selectivity demonstrates the applicability of the ZnO QDs and synthetic receptors for sweat analysis.